False Convictions - Ellsworth, Phoebe C. (2012)
False convictions have received a lot of attention in recent years. Two-hundred and forty-one prisoners have been released after DNA testing has proved their innocence, and hundreds of others have been released without DNA evidence. We now know quite a bit more about false convictions than we did thirty years ago - but there is much more that we do not know, and may never know